2009
DOI: 10.1038/pcan.2009.6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative predictors of blood loss at the time of radical prostatectomy: results from the SEARCH database

Abstract: The literature contains conflicting data on preoperative predictors of estimated blood loss (EBL) at radical retropubic prostatectomy (RRP). We sought to examine preoperative predictors of EBL at the time of RRP among patients from the SEARCH database to lend clarity to this issue. A total of 1154 patients were identified in the SEARCH database who underwent RRP between 1988 and 2008 and had EBL data available. We examined multiple preoperative factors for their ability to predict EBL using multivariate linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 20 publications
3
18
0
2
Order By: Relevance
“…Our findings of greater EBL in obese patients who underwent RRP are similar to those of previous studies [5-8]. Castle et al [27] reported a significant difference in operative time and blood loss according to BMI in 140 patients undergoing RALP.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings of greater EBL in obese patients who underwent RRP are similar to those of previous studies [5-8]. Castle et al [27] reported a significant difference in operative time and blood loss according to BMI in 140 patients undergoing RALP.…”
Section: Discussionsupporting
confidence: 91%
“…However, obesity may be a complicating factor in retropubic radical prostatectomy (RRP), resulting in higher complication rates, greater blood loss, higher transfusion rates, and worse functional results [5-8]. …”
Section: Introductionmentioning
confidence: 99%
“…We calculated the percent increase in EBL for every 5‐cmH 2 O increase in PEEP by using the formula (1 – 5 × exp(β)) × 100 if β < 1 and (5 × exp(β) − 1) × 100 if β > 1. Models were stratified by surgery type (RRP or RALP), and crude data were adjusted for BMI (log‐transformed), prostate weight (log‐transformed), year of surgery and surgeon, as these are factors that were previously shown to influence EBL in this population . All covariates were entered into the multivariable model.…”
Section: Methodsmentioning
confidence: 99%
“…Also, blood transfusions have been linked to cancer progression . In addition, brisk bleeding intraoperatively can obscure the surgeon's field, potentially causing the surgeon to operate more quickly, excise less tumor or inadvertently injure a nearby structure . It is important to identify potential modifiable risk factors for blood loss and attempt to minimize them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation